Being mortal : medicine and what matters in the end - Gawande, Atul (New York : Metropolitan Books, Henry Holt & Company, 2014)
A prominent surgeon argues against modern medical practices that extend life at the expense of quality of life while isolating the dying, outlining suggestions for freer, more fulfilling approaches to death that enable more dignified and comfortable choices.
The independent self -- Things fall apart -- Dependence -- Assistance -- A better life -- Letting go -- Hard conversations -- Courage.
Includes bibliographical references (pages 265-277).
Keywords: Terminal care; Aging; Death; Terminal Care; Activities of Daily Living; Aged; Aging -- physiology; Attitude to Death; Prognosis; Quality of Life; Terminal care; Aging; Death